CORRELATION BETWEEN ROOT COMPLEX MORPHOLOGY AND SURGICAL EXTRACTION OF MANDIBULAR THIRD MOLARS - Dervishova, Sandra; Mencheva, Zhaklina; Markovska Arsovska, Mirjana M; Temelkova, Simona; Stojanova, Irena (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Introduction: An impacted tooth is a tooth that has not erupted in the oral cavity, that is, its eruption is prevented for some reason. These are teeth that, throughout their development and under the influence of biological, dynamic and mechanical factors of genetic and phylogenetic origin, show variations in their number, size and degree of development. Material and methods:  This paper included 80 patients who were divided into 2 groups of 40 patients each according to the degree of impaction and analyzed how the morphology of the root complex is affected by the surgical technique used during extraction. Results:  The results show that the easiest surgical intervention is when the morphology of the root complex is a single conical root or the roots are joined in a conical shape, or even distally bent, because it is not necessary to separate them to extract the impacted tooth in its entirety and at the same time the possibility of apical fracture is avoided. Conclusion: The oral surgical procedure for extraction of impacted mandibular molars is not correlated with the morphology of the root complex but rather depends on the experience of the surgeon. Key words: impacted mandibular third molar, root complex morphology, operative surgical procedures, flap, separation.